Mechanical Bowel Preparation (MBP) Prior to Elective Colorectal Resections in Crohn's Disease Patients. Issue 4 (24th February 2018) - Iesalnieks, Igors; Hoene, Melanie; Bittermann, Theresa; Schlitt, Hans J; Hackl, Christina
Abstract: Background: Studies addressing the role of mechanical bowel preparation (MBP) in Crohn's disease (CD) patients are lacking. Methods: Consecutive elective colorectal resections for CD have been included in the present analysis. Exclusion criteria were small bowel resections not including colon, urgent surgeries, surgeries for cancer, and abdominoperineal resections for perianal disease. MBP was performed routinely between 1992 and 2004, omitted between 2005 and 2015, and reintroduced in 2016.Intraabdominal septic complications (IASC) were anastomotic leakage, intraabdominal abscess, intestinal fistula, and peritonitis. Results: Overall, 680 bowel resections for CD have been performed between 1992 and 2017. After exclusion of the abovementioned patients, 549 patients were included in the present analysis. The IASC rate was 12% in patients undergoing surgery after MPB as opposed to 24% when MBP was omitted ( P < 0.001). By the multivariate analysis, preoperative MBP significantly reduced the risk of IASC (Hazard ratio 0.45; 95% CI, 0.23 – 0.86; P = 0.016). Preoperative weight loss (HR 2.0; 95% CI, 1.1 – 3.6; P = 0.024), penetrating disease (HR 2.6; 95% CI, 1.3 – 5.4; P = 0.01), and stapled as opposed to hand-sewn ileocolic anastomosis (HR 3.3; 95% CI, 1.4 – 7.7; P = 0.006) were associated with an increased risk of IASC. The positive impact of MBP was strongest on anastomotic complication rate in patients undergoing ileocolic resections for penetrating disease (11% vs 36%, P < 0.001). Conclusion: Preoperative MPB should be strongly considered before colorectal surgery in patients with CD, especially in patients undergoing ileocolic resections for penetrating disease.